Applying Six Sigma in foodservice organizations - Kivela, Jakša (Array, 2008)
Summary: This study investigated how a large foodservice organization successfully adopted the Six Sigma quality system from other industry applications in their foodservice environment. In addition, the study explored how different levels of the organization had contributed to the application and the perceived importance of such system within the organization. Review of the recent foodservice lite-rature suggested that quality service research is important because it is directly linked to customer satisfaction and return patronage behaviors. However, the literature also revealed that there was little theoretical understanding of quality systems and applications in the foodservice industry that would be akin to Total Quality Management (TQM) and that such systems were mainly to be found in other service and manufacturing organizations e.g. banking, insurance and electronics industries. The study also revealed that here was a lack of systematic quality measures in existence in foodservice operations, although exceptions did exist such as in fast food like operations and more recently at a hotel group. Therefore, the aim of this study was to evaluate and assess how a Six-Sigma-hybrid quality system was adapted and introduced in a typical foodservice operation. In this study, the Hong Kong Jockey Club's introduction of the Six Sigma-type quality initiatives called the "Journey Toward Excellence" or JTE, were assessed and analyzed